Effects of Candidate Gender and Qualification on Hiring Recommendations in Asynchronous Video Interview Tools - Edurne Martínez-Moreno; Edurne Elgorriaga; Lorena Gil de Montes; Olaia Larruskain-Mandiola (Journal of Work and Organizational Psychology)

(untitled)
The main objective of this study is to examine the relative influence of candidate competencies vs. rater biases on hiring recommendations made using asynchronous video interview (AVI) tools, while considering a candidate's gender and qualifications. A 2 × 2 within-subject design was employed with 151 HR professionals in Spain to explore the effects of candidate gender (female vs. male) and qualifications (highly qualified vs. semi-qualified) on hiring recommendations. Binary logistic regression and qualitative analyses revealed that although competencies play a strong role biases were the dominant factor influencing hiring recommendations for all candidates. For women, competence was a key predictor. Sociability predicted hiring recommendation of semi-qualified candidates, particularly men, for whom morality also played an important role. First impressions favoured highly qualified women, while nonverbal communication favoured highly qualified men. Consistent with role congruity theory, communal competencies were more valued in women, while agentic competencies were crucial for men.